Pengaruh Intervensi Pelibatan Keluarga Terhadap Kecemasan Anak yang Mengalami Hospitalisasi di Ruang Perawatan Anak RSUD dr. Rasidin Padang Tahun 2016: The Effect of Family Involvement Intervention on Children's Anxiety Experiencing Hospitalization in the Child Care Room of Dr. Rasidin Hospital Padang in 2016 - Hermalinda; Dwi Novrianda; Mike Aulia Pratama Putri (Fakultas Keperawatan Universitas Andalas, 2017)
The Reaction of Anxiety is common in children during hospitalization and can affect the health status of children, adaptation and development problem. Family involvement is one of the intervention to decrease children anxiety to hospitalization. The purpose of this study is to determine the effect of family involvement intervention to children who experience the anxiety due to the hospitalization in child ward dr Rasyidin Padang. The study design is quasi-experiment, with pre-test post-test design approach without control group. The study was conducted In January until June, 2016. The sample of this study are 12 children who undergo hospitalization in child ward. Family involvement is given as intervention and it consists of 2 section. Data were collected using a questionnaire about anxiety level of children before and after intervention. Data were analyzed with using paired t-test. The results showed that the differences scores of anxiety level of children before and after family involvement intervention (p value: 0,002). Family involvement intervention can be considered as one intervention to children who experinces hosppitalization stress.